Genomic transition to pathogenicity in chytrid fungi. - Suzanne Joneson; Jason E Stajich; Shin-Han Shiu; Erica Bree Rosenblum (PLoS Pathogens, 2011)
Understanding the molecular mechanisms of pathogen emergence is central to mitigating the impacts of novel infectious disease agents. The chytrid fungus Batrachochytrium dendrobatidis (Bd) is an emerging pathogen of amphibians that has been implicated in amphibian declines worldwide. Bd is the only member of its clade known to attack vertebrates. However, little is known about the molecular determinants of - or evolutionary transition to - pathogenicity in Bd. Here we sequence the genome of Bd's closest known relative - a non-pathogenic chytrid Homolaphlyctis polyrhiza (Hp). We first describe the genome of Hp, which is comparable to other chytrid genomes in size and number of predicted proteins. We then compare the genomes of Hp, Bd, and 19 additional fungal genomes to identify unique or recent evolutionary elements in the Bd genome. We identified 1,974 Bd-specific genes, a gene set that is enriched for protease, lipase, and microbial effector Gene Ontology terms. We describe significant lineage-specific expansions in three Bd protease families (metallo-, serine-type, and aspartyl proteases). We show that these protease gene family expansions occurred after the divergence of Bd and Hp from their common ancestor and thus are localized to the Bd branch. Finally, we demonstrate that the timing of the protease gene family expansions predates the emergence of Bd as a globally important amphibian pathogen.